Exploring the Issue of ‘Run-away Women’ in Pakistan: A Call for Social and Legal Change - Hussain, Amjad; Afzal, Humaira (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2015)
Women are considered as vulnerable members of almost every society. In Pakistan the scenario is no different. ‘Run-away women’ is one of the socio-legal problems faced by women. Women who consider running away from their families often face difficult situations, which may result in being trapped into prostitution or even being murdered by their own families in certain cases. In runaway cases, the majority of women do return to their families after reconciliation. However, what happens to these women after reconciliation remains unknown. This paper aims to highlight the causes of running away and its consequences in Pakistani society. It also intends to examine the existing legal mechanisms and their role in dealing with this problem. This study also analyzes the Islamic and customary laws of Pakistan to identify whether both respect the decisionmaking authority and freedom of women, or whether they create any hindrances to women’s rights and their freedom to decide. Finally, measures for improvements in the legal and social system are suggested. analyzes the Islamic and customary laws of Pakistan to identify whether both respect the decision-making authority and freedom of women, or whether they create any hindrances to women’s rights and their freedom to decide. Finally, measures for improvements in the legal and social system are suggested. Key words: runaway women, runaway girls, runaway marriage, women’s rights, women’s protection